Repotenciación de un banco de pruebas de control, neumático y electroneumático, para el desarrollo de prácticas de laboratorio. - Peralvo Velasco, Diego Santiago (2020)
The technological advance at the industrial level have contributed that pneumatic actuators (cylinders) are one of the most suitable and economical elements for the development of an automation process and are fully automatic by improving production, this has been achieved with the implementation and installation of different automation systems such as so-called Programmable Logic Controllers (PLC) in their systems, installations, and machines obtaining more reliable control and monitoring in each of its productive stages. The lack of modules very well equipped with the necessary elements to carry out laboratory practices and poor distribution of them, both pneumatic and electromagnetic control of the above leads to the repowering of a bank of pneumatic control and electro-pneumatic tests for the development of laboratory practices, using the bibliographic method for the compilation of the information necessary to support the repowering of the testing bench. In addition, the descriptive method permitted to describe the laboratory practices of the content of pneumatic and electro-pneumatic control subject matter. The scientific method determined the poor distribution of the pneumatic and electro-pneumatic control elements, so for the testing bench repower, it was considered pneumatic, electro-pneumatic, control and electric system. Finally, it was repowered by testing bench, which helped to apply the minimum contents of the subject because of the equipment installed contribute to the appropriate use and correct distribution of each elements in order to carry out the laboratory practices different from the old testing benches